Die keuring van kandidate vir teologiese opleiding: Noodsaak en toepassing - Cooke, Frank T. (HTS teologiese studies, 2010)
The selection of candidates for theological training: Necessity and application The selection of candidates for theological training is a sensitive issue, as many see it as a verdict on the authenticity of the prospective student’s claim of having been called to ministry by God. This article argues that, in addition to a sense of calling, the profile of a candidate should include abilities in terms of office (power), profession (capability) and person (adequacy). The process of selection should involve all these aspects. The guidelines of the Dutch Reformed Church in South Africa in this regard in its publication, A–Z Handleiding aangaande predikante van die Nederduitse Gereformeerde Kerk, are discussed. The selection process should not be seen as a test of the authenticity of candidates’s sense of calling, but rather as a way in which candidates can be guided to discern their calling and place within the body of Christ. A positive outcome in the areas of office, capability and adequacy could confirm the claim of having been called by God. The article concludes that the selection of candidates for theological training is not a single event, but a process that starts when the prospective candidate reports to the church council, and is completed with the pastor’s ordination by the church.